Radiojornalismo e internet um estudo da rádio Catarinense AM da cidade de Joaçaba - Lesnieski, Marlon Sandro (Universidade do Vale do Rio dos Sinos, 2012)
The objective of this research is to understand how to configure the radio journalism in a radio station in the inner of Santa Catarina from the use of the internet by the professionals involved in the production routines of the newsroom of this radio. Centralize our efforts on two perspectives: first, changes in the information inserted in the digital context, and second, changes in journalistic use of the internet originated in the newsroom. We chose to study the radio Catarinense AM from the city of Joaçaba, we chose this station because, besides being a radio inside, it outlines an attempt to use the internet as a differential element in the daily production of its content of radio broadcasting. To study these processes of change, we use a range of methodological contributions, as the literature review, participant observation, data collection on the Internet and sound material of the station. It is concluded that the use of digital technologies in production radiojournalism leads to changes in the routines of news professionals involved in the investigation in a unique way, due to the unique characteristics taking place from the processes of convergence and midiamorphosis that are not homogeneous in all stations, but, only elements with respect to the needs of emerging each vehicle communication.
Keywords: Rádio; Jornalismo; Internet; Convergência; Journalism; Convergence; ACCNPQ::Ciências Sociais Aplicadas::Comunicação